PENGARUH CURRENT RATIO DAN ARUS KAS DARI AKTIVITAS OPERASI TERHADAP HARGA SAHAM DENGAN RETURN ON ASSET (ROA) SEBAGAI VARIABEL INTERVENING - Wuriyanti, Novi (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
The purpose of this study was to determine the effect of current ratios and cash flow from operating activities on stock prices with return on assets as an intervening variable in banking companies listed on the IDX for the 2017-2019 period. Population of 43 companies. The sampling technique is purpose sampling. Samples obtained by 25 companies. The data analysis technique used is descriptive statistical analysis, classical assumption test, hypothesis testing and path analysis. The results showed that CR has a positive and significant effect on ROA, while AKO has a positive and insignificant effect on ROA. AKO has a positive and significant effect on stock prices, while ROA and CR have a positive and insignificant effect on stock prices. ROA cannot mediate CR and AKO on share prices in banking companies listed on the IDX for the 2017-2019 period. Keywords: Current Ratio (CR), Cash Flow from Operating Activities (AKO), Return On Asset (ROA) and Stock Prices.